2019
DOI: 10.1371/journal.pone.0221647
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer produced from abattoir waste can contribute to phosphorus sustainability, and biofortify crops with minerals

Abstract: Our food security depends on finding a sustainable alternative to rock phosphate for fertilizer production. Furthermore, over 2 billion people worldwide are currently affected by micronutrient deficiencies, and crop concentrations of essential minerals are declining. This paper examines whether a novel multi-element fertilizer, Thallo ® , can produce crop yields comparable to conventional rock phosphate derived fertilizers, and have an additional benefit of increasing essential mineral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Rumen contents were mostly piled into pits and sold as manure for peri-urban agriculture by 59% of the respondents. This is in line with the findings by Darch et al (2019) that fertilizers produced from abattoir wastes contribute to the plants mineral requirements for proper growth. Only 16% of the respondents sold dried rumen contents for livestock feeds.…”
Section: Fig 2 Do You Separate Discarded Carcasses From Rumen Contesupporting
confidence: 92%
“…Rumen contents were mostly piled into pits and sold as manure for peri-urban agriculture by 59% of the respondents. This is in line with the findings by Darch et al (2019) that fertilizers produced from abattoir wastes contribute to the plants mineral requirements for proper growth. Only 16% of the respondents sold dried rumen contents for livestock feeds.…”
Section: Fig 2 Do You Separate Discarded Carcasses From Rumen Contesupporting
confidence: 92%
“…This may be intra-annual, as species differ in their heading date, or inter-annual, as some species are less persistent than others [49]. Grassland management, such as the application of lime or fertilizers, is also known to affect mineral concentrations of swards [23], and there is a lack of knowledge on mineral concentrations required in different soil types, and antagonistic effects between minerals [50]. It is also necessary to further investigate the effect of grazing management, which can affect the ratio of leaves and stems in the sward, the former being known to contain higher concentrations of minerals [51], and thus affect the mineral content of the sward.…”
Section: Wider Considerationsmentioning
confidence: 99%
“…i [51] ireported similar results in a greenhouse experiment on AWW on maize. In a previous study, concentrations of nutrients, including N, P, K, Ca, Mg and Na were found higher in Lolium perenne and Triticum aestivum grown in soil treated with fertilizer produced from abattoir wastes [17]. Also, Matheyarasu and Bolan [47] reported the application of AWW to cause an abundance of nutrient accumulation in Pennisetum purpureum, Medicago sativa, Sinapis alba and Helianthus annuus.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, yield improvement in plants grown in wastewater treated soil conforms to that of Matheyarasu and Bolan [47] who found about 70% lower yields in Pennisetum purpureum, Medicago sativa, Sinapis alba and Helianthus annuus grown under tap water compared to the abattoir wastewater irrigation. Similarly, in a pot experiment, fertilizer produced from abattoir waste products was found to significantly increase biomass yield of AberMagic grass (Lolium perenne) and wheat (Triticum aestivum) compared with the Nil treatment pots [17]. They reported more grain production in wheat and AberMagic grass when AWW was applied and concluded that it is a sustainable alternative to conventional fertilizers.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation